WCDMA downlink capacity improvement by using smart antenna - Tiong, Sieh Keong; Ismail, Mahamod; Hassan, Azmi (IEEE, 2005)
Heterogeneous type of users in modern mobile communication expect network service provider providing high-speed data, multimedia and voice services. However, capacity has always been an issue to any generation of mobile communication technologies as it is always inversely proportionate to QoS (quality of service) in nature. Hence, in order to increase the system capacity without jeopardizing the QoS, smart antenna was proposed to increase the spectral efficiency of the wireless channel. Many research works have shown that the system capacity of modern mobile communication can be improved by employing smart antenna [1][2]. A dynamic radio network simulator was developed in Visual C++® to study and estimate the downlink capacity of a WCDMA system with smart antenna. Capacity system by using different smart antenna strategies was studied in this research. Simulation was done based on single micro cell environment with considering interference from the first tier. User mobility is taken into account to provide a combined evaluation of Radio Resource Management (RRM). Capacity system expressed in downlink outage under various simulation scenarios was represented in this paper